Efficacy and Safety of ACE Inhibitor and Angiotensin Receptor Blocker Therapies in Primary Focal Segmental Glomerulosclerosis Treatment: A Systematic Review and Meta-Analysis - Campbell, Kirk N; Pennese, Natali; Zaffalon, Andrea; Magalhaes, Barbara; Faiella, Marina; Caster, Dawn J; Radhakrishnan, Jai; Tesar, Vladimir; Trachtman, Howard (Kidney medicine, 2022)
RATIONALE AND OBJECTIVE: Angiotensin-converting enzyme inhibitor or angiotensin receptor blocker therapy (renin-angiotensin-aldosterone system [RAAS] inhibitor) to control proteinuria in primary and genetic focal segmental glomerulosclerosis (FSGS) follows guidelines based on other proteinuria-related kidney diseases. There is no consensus on the efficacy and safety of RAAS inhibitor therapies in primary and genetic FSGS. This systematic review assessed the effects of RAAS inhibitor therapy on kidney outcomes in these patients. STUDY DESIGN: Systematic review of randomized controlled trials, interventional nonrandomized studies, observational studies, and retrospective studies. SETTING & STUDY POPULATIONS: Patients with primary and genetic FSGS. SELECTION CRITERIA FOR STUDIES: PubMed, Cochrane Library, and Embase. DATA EXTRACTION: 2 investigators independently screened studies and extracted data. ANALYTICAL APPROACH: Results were summarized as the ratio of means (ROM) between baseline and follow-up measurements or as the hazard ratio using random-effects models. RESULTS: 30 publications were selected; 5 were controlled trials (4 randomized controlled trials). 8 assessed RAAS inhibitor monotherapy, while the rest studied RAAS inhibitors in combination with other drugs, mainly immunosuppressants. On average, a 32% proteinuria reduction (ROM, 0.68; 95% CI, 0.47-0.98) and no change in creatinine clearance (ROM, 0.95; 95% CI, 0.77-1.16) from baseline to the last reported follow-up was observed in patients treated with RAAS inhibitor monotherapy. When a RAAS inhibitor was combined with other drugs, a 72% proteinuria reduction was observed from baseline to the last reported follow-up (ROM, 0.24; 95% CI, 0.08-0.75). The published data did not allow for the assessment of the effects of RAAS inhibitor monotherapy on estimated glomerular filtration rate and end-stage kidney disease risks. LIMITATIONS: Large study heterogeneity in design, patient populations, and treatment regimens. No access to individual patient-level data. CONCLUSIONS: This review supports the tendency to observe a proteinuria reduction with RAAS inhibitors in patients with primary FSGS. RAAS inhibitor monotherapy was associated with maintained kidney function, as shown by no change in creatinine clearance. Strong evidence to quantify the effects of RAAS inhibitor monotherapy on end-stage kidney disease and glomerular filtration rate was lacking. Larger, well-designed clinical trials are needed to better understand the effects of RAAS inhibitors on primary FSGS.
Keywords: end-stage renal disease; focal segmental glomerulosclerosis; proteinuria; End-stage kidney disease; renin-angiotensin-aldosterone system inhibitor